Angioedema. Interdisciplinary diagnostic and therapeutic recommendations of the Polish Dermatological Society (PTD) and Polish Society of Allergology (PTA) - Nowicki, Roman; Grubska-Suchanek, Elżbieta; Porębski, Grzegorz; Kowalski, Marek L.; Jahnz-Różyk, Karina; Matuszewski, Tomasz; Rudnicka, Lidia; Kulus, Marek; Barańska-Rybak, Wioletta; Czajkowski, Rafał; Doniec, Zbigniew; Kowalewski, Cezary; et al. (Dermatology Review/Przegląd Dermatologiczny, 2020)
Angioedema is a non-inflammatory edema of the subcutaneous tissue and/or mucosal membranes. It commonly coexists with urticaria and is considered a deep form of urticaria. Less commonly, it occurs as an isolated disease in one of two basic forms: acquired angioedema and hereditary angioedema. Four types of acquired angioedema and seven types of hereditary angioedema were difinied. The treatment of angioedema depends on its form and etiological factors, with hereditary angioedema posing a most significant challenge.